Atelocollagen Injection Enhances the Healing of Nonoperatively Treated Achilles Tendon Tears - Jaehwang Song MD, PhD; Chan Kang MD, PhD; Seongkyeong Jo MS (Foot & Ankle Orthopaedics)
Category: Basic Sciences/Biologics; Sports Introduction/Purpose: There is growing interest in nonoperative treatment for the management of Achilles tendon ruptures (ATRs). However, nonoperative treatment is limited by the risk of tendon reruptures and low satisfaction rates. Recently, atelocollagen injections have been reported to have beneficial effects on tendon healing. The purpose of this study is to evaluate the beneficial effects of injected atelocollagen on Achilles tendon healing and investigate the mechanism of atelocollagen on tendon healing. Methods: Percutaneous tenotomy of the right Achilles tendon in 66 rats was performed. The animals were equally divided into the noninjection group (NG) and the collagen injection group (CG). At 1, 3, and 6 weeks, the Achilles functional index (AFI), cross-sectional area, load to failure, stiffness, stress, and the modified Bonar score were assessed. Transmission electron microscopy (TEM), western blotting, and immunohistochemistry were also performed. Results: The AFI (–6.8 vs 243.0, respectively; P = .040), load to failure (42.1 vs 27.0 N, respectively; P = .049), and stiffness (18.8 vs 10.3 N/mm, respectively; P = .049) were higher in the CG than those in NG at 3 weeks. There were no significant differences in histological scores. TEM analysis showed that the mean diameter of collagen fibrils in the CG was greater than that in the NG at 3 weeks (117.2 vs 72.6 nm, respectively; P < .001) and 6 weeks (202.1 vs 144.0 nm, respectively; P < .001). Western blot analysis showed that the expression of collagen type I in the CG was higher than that in the NG at 1 week (P = .005) and 6 weeks (P = .001). Conclusion: An atelocollagen injection had beneficial effects on the healing of nonoperatively treated Achilles tendon injuries. The Achilles tendon of CG rats exhibited better functional, biomechanical, and morphological outcomes compared with NG rats. The molecular data indicated that the mechanism of atelocollagen injections may be associated with an increased amount of collagen type I. The scheme and the outcomes of the present study 1. The flowchart of the experiment groups and surgical procedures involved in this study. 2. Functional analysis. 3. Biomechanical testing. 4. Histological analysis. 5. Transmission electron microscopy (TEM) analysis. 6. Western blot analysis.